2015
DOI: 10.1111/ijd.12496
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related characteristics of cutaneous melanoma in a Spanish Mediterranean population

Abstract: Our results suggest that melanoma development in younger patients is the result of genetic factors, particularly related to multiple nevi, whereas in older patients environmental factors such as severe chronic sun exposure play a major role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
4
10
1
Order By: Relevance
“…Our SEER analysis shows that with increasing age, primary melanomas exhibit increased thickness and more unfavorable pathologic features, leading to more advanced stages, increased mortality, and worse MSS, independent of gender and stage at diagnosis. This validates an analysis of 13,581 patients in the AJCC melanoma database in which age was the third most significant prognostic factor for localized melanomas after thickness and ulceration [ 28 30 ].…”
Section: Discussionsupporting
confidence: 77%
“…Our SEER analysis shows that with increasing age, primary melanomas exhibit increased thickness and more unfavorable pathologic features, leading to more advanced stages, increased mortality, and worse MSS, independent of gender and stage at diagnosis. This validates an analysis of 13,581 patients in the AJCC melanoma database in which age was the third most significant prognostic factor for localized melanomas after thickness and ulceration [ 28 30 ].…”
Section: Discussionsupporting
confidence: 77%
“…We hypothesize this observation could be due to either a site-specific higher melanocyte proliferation, to the influence of greater sun exposure at this area, or due to a combination of both factors. The strong link between nevus density, primary melanoma site and a prior history of sunburn or intermittent UVR exposure at the same site support the role of sun exposure as a trigger for melanoma development in an already predisposed area [ 30 32 ]. The present findings suggest that areas with a high nevus density that have suffered mild or intense sunburns should be clinically examined more carefully, and should probably need to be more meticulously sun protected in order to prevent the increase in the number of nevi, an approach which has been proven especially useful in fair-skinned, freckle-prone patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…3,8 Although numerous risk factors have been associated to the development of MM (including light eyes and low skin phototypes, presence of dysplastic naevi, tendency to freckle and family history of melanoma), the significance of some associations remains unclear, particularly in aged subgroups. [3][4][5] The risk associated with sun exposure and multiple naevi, for example, are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] The risk associated with sun exposure and multiple naevi, for example, are controversial. 8,9 Traditional prognostic factors for cutaneous MM include thickness, ulceration, mitoses/mm 2 , clinical stage, anatomic location, sex and age, 10 and although some pathologic features were previously linked to lower disease specific survival rates, 4,5,7,10 some associations remain uncertain in older patients. 10 In accordance to our findings, several studies suggested that melanoma is more common in older men; 3,4,6-8,10 they have focused on histologic features and/or survival, and few evaluated risk factors for melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation